A new pest of lychees in New Caledonia. Issue 1 (2nd January 2017) - Marchal, L.; Cazères, S.; Kergoat, G. J.; Letellier, K.; Mitchell, A.; Nattier, R.; Mille, C.
ABSTRACT: A new and very occasional pest of lychee trees ( Litchi chinensis ) was recently identified from New Caledonia—the endemic weevil Acanthopygus griseus Montrouzier, 1861 (Coleoptera: Anthribidae). This is the first report of an anthribid weevil causing significant damage to living trees.